2023 NIGERIA’S (PRESIDENTIAL) ELECTION: DOMESTIC IMPACTS AND FOREIGN POLICYIMPLICATION FOR CONSOLIDATION - Mustapha, Ayodele Haruna; Oluwatukasi, Eyiyemi Bukola; Ayegbusi, Talabi Rasheed (EBSU Journal of Social Sciences and Humanities, 2024)
Elections are terminal events in which competitive political activities are galvanized towards the race into government offices in many democratic countries ,where political parties struggle for power among themselves for the control of government (statecraft) for subsequent years. All these come with intensive, aggressive, and high-spirited manners employed by stakeholders in elections management, electorates, and political elites. Nigeria is not an exception, as it is in the 24th year of the Fourth Republic of democratization practices, consolidation efforts for popular participation, and collective governance with their principles. This paper interrogates the 2023 General elections, their efficacy, issues, problems, and prospects for sustainable political growth in Nigeria. The paper examines the domestic impacts towards the election, before, during, and shortly after the emergence of the winner as announced and declared by the Independent National Electoral Commission (INEC). Likewise, it noted the external implications on the conduct of the elections as the dynamics of the exercise shaped her national interest and foreign policy disposition to the world. The paper therefore posits to identify as domestic factors – the rise of ethnic /religious cleavages, weak political institutions, voters’ perceptions, vote buying and ballot-box snatching syndromes, identity crisis issues, post–election crises while the foreign policy implication evolved from insecurity, kidnapping, banditry, corruption, state fragility, high rate of piracy, border trafficking in drugs and persons, low compliance to the rule of international law, unstable economic and social policies, image crisis and perceptions of foreign observers to the elections. The paper recommends government policy options like providing an enabling environment for political stability, the rule of law to operate freely and fairly, trust in the judiciary, reduction in economic, social, and political tensions, avoidance of ethnic and primordial interests as variables tools for domestic politics, while genuine efforts in the confidence building, increase in foreign capital flow, diaspora inputs, legitimacy, and security guarantee. The study makes use of secondary sources to elicit data, while it adopts political legitimacy theory and the pluralist theory of democracy to mid–wife the study.